The spread of the invasive mosquito Aedes albopictus (Diptera: Culicidae) in Portugal - Zé-Zé, Líbia (2024)
Funding Information: This work was funded by the Institute of Environmental Health of the Faculty of Medicine of the University of Lisbon (ISAMB), with project references FCT UIDB/04295/2020 and UIDP/04295/2020. This work was partially funded by the MOBVEC\u2014Mobile Bio-Lab to support first response in Arbovirus outbreaks (2023\u20132026) project, reference HORIZON-EIC-2022-PATHFINDEROPEN-01 under the Pathfinderopen program of the European Innovation Council (CEI), and Ph.D. fellowship reference 2022.13476.BDANA (FCT). The funders had no role in study design, data collection and analysis, decision to publish, or manuscript preparation. Funding Information: We are grateful to Marco Brustolin and Carles Aranda for providing evidence of the collection date and location in Spain of the sampled mosquitoes corresponding to sequences KU319443, KU319444, KU319446, and KU319447. We also thank the REVIVE team for collecting mosquitoes nationwide, especially Lisbon and Tagus Valley Health Authority. This work received support from the Portuguese Foundation for Science and Technology (FCT; reference: CEECINST/00049/2021/CP2817/CT0001, DOI: https://doi.org/10.54499/CEECINST/00049/2021/CP2817/CT0001 ; reference: FCT/MCTES UIB/00211/2020, https://doi.org/10.54499/UIDB/00211 ; reference: FCT/MCTES UIP/00211/2020, https://doi.org/10.54499/UIDP/00211). Publisher Copyright: © The Author(s) 2024.